Shock Cooling and Possible Precursor Emission in the Early Light Curve of the Type II SN 2023ixf - Griffin Hosseinzadeh; Joseph Farah; Manisha Shrestha; David J. Sand; Yize Dong; Peter J. Brown; K. Azalee Bostroem; Stefano Valenti; Saurabh W. Jha; Jennifer E. Andrews; Iair Arcavi; Joshua Haislip; et al. (The Astrophysical Journal Letters, 2023)
We present the densely sampled early light curve of the Type II supernova (SN) 2023ixf, first observed within hours of explosion in the nearby Pinwheel Galaxy (Messier 101; 6.7 Mpc). Comparing these data to recently updated models of shock-cooling emission, we find that the progenitor likely had a radius of 410 ± 10 R _⊙ . Our estimate is model dependent but consistent with a red supergiant. These models provide a good fit to the data starting about 1 day after the explosion, despite the fact that the classification spectrum shows signatures of circumstellar material around SN 2023ixf during that time. Photometry during the first day after the explosion, provided almost entirely by amateur astronomers, does not agree with the shock-cooling models or a simple power-law rise fit to data after 1 day. We consider the possible causes of this discrepancy, including precursor activity from the progenitor star, circumstellar interaction, and emission from the shock before or after it breaks out of the stellar surface. The very low luminosity (−11 mag > M > −14 mag) and short duration of the initial excess lead us to prefer a scenario related to prolonged emission from the SN shock traveling through the progenitor system.